Evaluating Lateral Spreading Using Newmark Method Based on Liquefaction Triggering - Yanxin Yang; Junhua Chen; Zhenqiang Zhang; Jianlin Ma (Advances in Civil Engineering)
The prediction of liquefaction-induced lateral spreading is an important geotechnical engineering problem. In this paper, a simplified prediction method based upon Newmark sliding block analysis was proposed to predict the liquefaction-induced lateral spreading. The acceleration time history beneath the liquefied soil (starting from the triggering time of liquefaction) and the postliquefaction yield acceleration corresponding with the residual shear strength of liquefiable soil were used in the Newmark sliding block analysis. One-dimensional effective stress analysis was conducted to obtain the motion beneath the liquefied soil and the liquefaction time. Limit equilibrium analysis was employed to determine the postliquefaction yield acceleration using the residual shear strength of liquefied soil, which correlated with the equivalent clean sand SPT blow count of the liquefied sand. This method was evaluated against five well-documented case histories and the predicted displacements of lateral spreading were subsequently compared with the observed displacements. In addition, the lateral spreading predicted by the rigorous Newmark sliding block method and numerical difference analysis was presented. Based on the statistical analysis of the displacement ratios, it suggested that the method proposed in this paper identified the triggering time of liquefaction and provided a reasonable prediction of the liquefaction-induced lateral spreading with an RMSE (root mean square error) of 0.63, a standard deviation of 0.40, and a CV (coefficient of variance) of 0.60, respectively.